Student’ Perceptions of Rhythmic Gymnastics Learning in Physical Education at SMAIT IQRA Kota Bengkulu - Oetari Lismana; Megi Personi; Titi Ajayati (Jurnal Pendidikan Rafflesia, 2026)
This study aims to explore students’ perceptions of rhythmic gymnastics learning in Physical Education, Sports, and Health (PJOK). A qualitative approach with a phenomenological design was employed to understand students’ lived experiences. The participants consisted of 10 students from grades X-XII at SMAIT IQRA Kota Bengkulu, selected through purposive sampling. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using the Miles and Huberman interactive model. The findings reveal that students’ perceptions are categorized into cognitive, affective, and psychomotor dimensions. Positive perceptions arise from enjoyment, physical benefits, and new learning experiences, while negative perceptions are associated with embarrassment, low self-confidence, and limited facilities. Teaching methods, social interaction, and prior learning experiences are identified as key influencing factors. The study highlights the importance of designing engaging and supportive rhythmic gymnastics instruction to enhance student participation.